2007
DOI: 10.1002/jcp.21297
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans retinoic acid prevents angiotensin II‐ and mechanical stretch‐induced reactive oxygen species generation and cardiomyocyte apoptosis

Abstract: Cardiomyocyte apoptosis has an important role in the transition from compensatory cardiac remodeling to heart failure. All-trans retinoic acid (RA), a bioactive vitamin A derivative, prevents stretch- and angiotensin II (Ang II)-induced cardiac hypertrophy. However, the anti-apoptotic potential of RA in the heart remains unexplored. Here, we demonstrate that stretch- and Ang II-induced apoptosis is prevented by RA in neonatal cardiomyocytes. RA improved mitochondrial function by inhibiting the stretch- and Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 46 publications
6
48
0
1
Order By: Relevance
“…The atRA treatment has been shown to up-regulate superoxide dismutase (Choudhary et al 2008a). This was strongly supported from a previous observation that atRA treatment prevented AngII-induced oxidative stress in cardiomyocytes (Choudhary et al 2008b). Therefore, the conclusion was that reduction of the oxidative stress by retinoic acid nullified the AngII-mediated cellular damage and inhibited cellular apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…The atRA treatment has been shown to up-regulate superoxide dismutase (Choudhary et al 2008a). This was strongly supported from a previous observation that atRA treatment prevented AngII-induced oxidative stress in cardiomyocytes (Choudhary et al 2008b). Therefore, the conclusion was that reduction of the oxidative stress by retinoic acid nullified the AngII-mediated cellular damage and inhibited cellular apoptosis.…”
Section: Discussionsupporting
confidence: 73%
“…They also first reported the evidence that ATRA prevented angiotensin IIand stretched-induced apoptosis. 27 He et al 28 found that ATRA inhibited the angiotensin II-induced increase in cell growth and collagen secretion in neonatal rats with cardiac fibroblasts. Haxsen et al 29 reported that ATRA could inhibit the actions of angiotensin II on vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…RA also plays a role in maintaining the integrity of hematopoietic cells (Oritani et al, 1992) and retinal precursors (Kholodenko et al, 2007). RA may prevent cardiac remodeling and ventricular hypertrophy by inhibiting the production of angiotensin II and ROS formation and by increasing antioxidant defenses (Choudhary et al, 2008). Different anti-apoptotic genes have been identified as retinoid responsive, such as SOD-2 in neuroblastoma and acute myeloblastic leukemia cells (Kiningham et al, 2008), B-cl2 in leukemic cells (Yin et al, 2005), Trx in airway epithelial cells (Chang et al, 2002) and GPx-2 in human breast cancer cells (Chu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%